Vertically emitting microdisk lasers - Mahler, Lukas; Tredicucci, Alessandro; Beltram, Fabio; Walther, Christoph; Faist, Jerome; Witzigmann, Bernd; Beere, Harvey E.; Ritchie, David A. (Nature Photonics, 2009)
In microdisk lasers a ring resonator is formed by successive total internal reflections inside a circularly shaped waveguide. The photon lifetime of the resulting whispering gallery optical modes is limited mainly by the waveguide absorption. Light is usually coupled out by tunnelling owing to the disk curvature or through imperfections at the border, but the output power is hard to exploit in a potential application because the emission is mainly in the disk plane and isotropic. Here we realize vertically emitting whispering gallery lasers by implementing appropriate diffraction gratings along the disk circumference. We use terahertz quantum cascade structures and demonstrate a 50-fold increase in the optical power compared to devices without gratings, while at the same time engineering the lasing spectrum according to the grating rotational symmetry. This concept will allow the fabrication of compact arrays of single-mode terahertz sources with regular beam profiles and high output power.
CRIS-Team Scopus Importer:2021-06-11